Defense Attorneys' Concerns about the Competence of Adolescent Defendants - Wingrove, Twila (Behavioral sciences & the law, 2010)
Research indicates that a sizable proportion of adolescent defendants have difficulty understanding and participating in legal proceedings against them, and may be incompetent to stand trial. To examine attorneys' experience in defending adolescents with competence-related difficulties, 214 juvenile attorneys were surveyed. Findings indicated that attorneys have doubts about the competence of approximately 10% of adolescent defendants, and that they find these cases particularly challenging to defend. Most attorneys appear to recognize that developmental factors may contribute to adolescents' competence-related difficulties, and believe that the law should accept developmental immaturity as a basis for incompetence findings. In approximately half of the cases in which attorneys had doubts about competence, attorneys did not request a competence evaluation but instead made other efforts to address competence issues, such as by teaching adolescents about legal proceedings and further involving their parents. The implications of these findings are discussed